Comparison of Aesthetic Appearance “after Urethral Mobilization and Snodgrass procedure in Hypospadias Surgery using HOPE SCORE - Asim ur Rehman, Ramzan Ejaz Rana, Ghulam Mohy ud Din, Saleem Ullah Khan, Rafiq Ahmad Kamran, Mahboob Ahmad Bhutta (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypospadias is a congenital anomaly in which the urethra, foreskin, and ventral penile structures fail to develop normally, resulting in an ectopic urethral opening. Objective: To compare postoperative urethrocutaneous fistula rates and cosmetic outcomes, measured using the Hypospadias Objective Penile Evaluation (HOPE) score, between Snodgrass repair and urethral mobilization in distal penile hypospadias. Methods: This randomized controlled trial was conducted over six months from October 2021 to March 2022 at The Children’s Hospital Lahore, following ethical approval and informed consent. Fifty-four patients were randomized equally: Group A underwent Snodgrass repair, and Group B received urethral mobilization. At final follow-up, standardized photographs (five views) were evaluated independently by two pediatric surgeons and one pediatric urologist using the HOPE scoring system. Results: Mean patient age was 4.63 ± 3.25 years in Group A and 4.48 ± 3.41 years in Group B. Urethrocutaneous fistula occurred in 2 patients (7.4%) in Group A and 1 patient (3.7%) in Group B (p = 0.552). HOPE scores favored the Snodgrass technique across several domains, including meatal shape (p = 0.032), glans configuration (p = 0.025), skin appearance (p = 0.028), torsion (p = 0.028), and penile curvature (p = 0.014). Conclusion: Snodgrass repair provides superior cosmetic outcomes compared with urethral mobilization, while both techniques demonstrate similar fistula rates in distal hypospadias surgery. Keywords: Urethrocutenous fistula, cosmetic outcomes, HOPE score, Snodgrass repair, Urethral mobilization technique, distal hypospadias surgery.